Pengaruh Massage Minyak Jahe Merah terhadap Skala Nyeri pada Pasien dengan Osteoarthritis - Pramesti, Kadek Diah; Ngurah, IGK Gede; Suardana, I Wayan; Sudiantara, Ketut; Gama, I Ketut; Lestari, Agus Sri; Achjar, Komang Ayu Henny; Mustika, I Wayan; Harini, I Gusti Ayu (Jurnal Gema Keperawatan, 2025)
Osteoarthritis is a degenerative disease of joint cartilage that causes pain. The aim of this study was to determine the effect of red ginger oil massage on the pain scale in patients with osteoarthritis. This research used pre-experimental research with one-group pre-posttest with purposive sampling technique with 35 populations. There were 33 samples were given massage treatment using 5-10cc of red ginger essential oil 2x a week for 2 weeks for 20 minutes. The results of this research show that the majority of respondents are 66-70 years old (54,5%), the majority are female (55,5%), the respondent's education is high school (60,6%), the respondent's occupation is trader (24,2%), and the majority of respondents suffered from osteoarthritis for one year (30,3%). The patient's pain scale before the red ginger oil massage was carried out was in the moderate pain category (72,7%) with an average pain scale of 4,12 and after the red ginger oil massage was carried out it was in the mild pain category (100%) with an average pain scale of 2,18. Based on the results of the Wilcoxon test, a p value of 0,000 (α=0,05) was obtained, so it can be concluded that there is an effect of red ginger oil massage on the pain scale in patients with osteoarthritis and a decrease in the pain scale of 1,94. Massage in synergy with the red ginger oil content applied to the skin will reach the blood circulation which can inhibit prostaglandin synthesis, so that pain subsides or inflammation is reduced. It is hoped that the results of this research can be used as an alternative measure in treating complaints of joint pain in osteoarthritis patients.